What Can Metaphor Tell Us About Experiences of Pregnancy Loss and How Are These Experiences Reflected in Midwife Practice? - Littlemore, Jeannette; Turner, Sarah (Frontiers in Communication, 2019)
With the recent launch of the National Bereavement Care Pathways in the UK http://www.nbcpathway.org.uk/pathways/ that are designed to help professionals to support families in their bereavement after any pregnancy loss, there has been an increased interest in aligning the care provided to the needs that are expressed by the bereaved parents. In order to do this we need in-depth knowledge of these experiences. In this paper, we report findings from a study, conducted in England, that explored the ways in which those who have experienced pregnancy loss talk about their experiences at different stages in the diagnosis and experience of pregnancy loss. We focus both on what they say and the language they use to describe their experiences, in order to gain that may make it easier for those who support them through the process to do so in an effective manner. We focus in particular on the metaphors they use to describe their experiences. Metaphors are often used by people when describing intensely painful, personal experiences that would otherwise be inexpressible. Exploring the metaphors used by the bereaved allows us to gain deeper insights into what they are going through and understanding these metaphors may allow us to support them more effectively. We also examined the accounts of midwives and other NHS maternity bereavement care practitioners in order to gain insights into their perspectives on the issues identified through our analysis of the metaphors used by the bereaved, and to identify areas of good practice which correspond to the experiences of the bereaved. We were interested in their own practice but also in the environment in which they work and the constraints that this sometimes brings.